Association between nutrient adequacy and psychosocial factors with overall rate of weight loss after bariatric surgery - Vanoh, Divya; Shahar, Suzana; Mahmood, Nik Ritza Kosai Nik (Asia Pacific journal of clinical nutrition, 2015)
This was a cross-sectional study that investigated the relationship between nutrient intake and psychosocial factors with the overall rate of weight loss after bariatric surgery among patients who had undergone sleeve gastrectomy in University Kebangsaan Malaysia Medical Centre (UKMMC). Forty-three subjects (15 men and 28 women) were recruited for this study. Subjects completed assessment questionnaires including the Binge Eating Scale (BES), Beck Depression Inventory (BECK), Family Support Questionnaires, and the Index of Peer Relation (IPR). Results showed that the median overall rate of weight loss was 4.3+/-5.5 kg/month, which was lower when compared to the rate of weight loss at three months which was 5.0+/-5.6 kg/month. Pre-operative weight was the predictor of overall rate of weight loss (p<0.05, R squared=0.52). Binge eating disorder (BED) and depression were also closely associated with each other after bariatric surgery (p<0.001, R squared=0.46). Subjects with good compliance to dietary advice had lower scores on the binge eating scale. The mean caloric and protein intake was very low, only 562+/-310 kcal/day and 29.6+/-16.1 g/day. The intake of vitamin A, B-1, B-2, B-3, B-12, C, folate, and iron met the Malaysian Recommended Nutrient Intake (RNI). However, the RNI for calcium, zinc, selenium, vitamin D, and vitamin E was not met. In conclusion, although bariatric surgery had many health benefits, several factors hindered weight loss after bariatric surgery. Health care professionals should closely monitor patients after bariatric surgery.